Clustering of colorectal neoplasia: characteristics of coexisting adenomas in patients with severely dysplastic polyps or invasive (malignant) polyps as compared to patients with benign adenomas or carcinomas. Issue 790 (August 1991) - Pines, A.; Bat, L.; Shemesh, E.; Rosenblum, J.; Horowitz, A.; Levo, Y.; Bubis, J. J.
Abstract : This study compared the size, histology and morphology of coexisting neoplastic polyps found in colonoscopy, and evaluated the clustering of these polyps in patients with either colorectal carcinoma, cancerous polyps or benign adenomas. Patients were divided by their most malignant form of neoplasia: Group A included 58 patients with early invasive cancerous polyps, and Group B included 73 patients with in situ carcinoma within an adenoma. Group C consisted of 335 patients with benign adenomas, and Group D had 289 patients with colorectal carcinoma. There were no significant differences between the four groups regarding sex, age and ethnicity. The cancerous polyps were significantly larger than the benign polyps. There were significantly (P less than 0.01) more patients with multiple (greater than or equal to 5) colonic lesions in Groups A or B than in Groups C or D. Coexisting polyps were much closer to the index growth, and demonstrated more severe dysplastic changes in the case of cancerous polyps than those associated with benign polyps or cancer. Based on our data we speculate that cancerous polyps are not merely a middle link in adenoma-carcinoma sequence, but rather mark a subset of patients who are especially prone to develop neoplastic changes in their colonic mucosa. These patients should be included in a more strict colonoscopic surveillance programme.